A novel orally available seleno-purine molecule suppresses triple-negative breast cancer cell proliferation and progression to metastasis by inducing cytostatic autophagy. Issue 8 (3rd August 2019) - Chang, Chia-Hao; Bijian, Krikor; Wernic, Dominik; Su, Jie; da Silva, Sabrina Daniela; Yu, Henry; Qiu, Dinghong; Asslan, Mariana; Alaoui-Jamali, Moulay A.
ABSTRACT: Patients with triple-negative breast cancer (TNBC) often have a poor prognosis largely due to lack of effective targeted therapy. Using a library of seleno-purines coupled to a high-throughput biochemical enzymatic assays we identified a potent pharmacological enhancer of autophagy (referred herein as SLLN-15) that selectively activated cytostatic macroautophagy/autophagy in TNBC preclinical models. SLLN-15 induced a dose-dependent anti-proliferative activity in the TNBC cell lines MDA-MB-231 and BT-20 via induction of autophagy and autophagic flux. This induction was associated with a selective inhibition of AKT-MTOR signaling. Conversely, rapamycin, a known autophagy inducer and MTOR inhibitor, was unable to duplicate SLLN-15's effect on TNBC cells. Inhibition of autophagy by siRNA-mediated targeting of the autophagy regulators, BECN1, ATG5 and ATG7 or using 3-methyladenine (3-MA), significantly protected against SLLN-15-induced inhibition of cell viability, further supporting that SLLN-15-induced inhibition of cancer cell proliferation was autophagy-dependent. SLLN-15-induced autophagy in TNBC cells was also associated with decreased AURKA expression, decreased AKT phosphorylation and subsequent blockage of the AKT-MTOR pathway. In vivo, oral SLLN-15 revealed a potent anticancer and anti-metastatic activity in mice bearing TNBC. Altogether, this study describes a novel regulator of mammalian autophagy, with potential utility as an experimental therapeutic for TNBCs. Abbreviations: 3-MA: 3-methyladenine; ATG5: autophagy related 5; ATG7: autophagy related 7; AURKA: aurora kinase A; AURKB: aurora kinase B; BECN1: beclin 1; CQ: chloroquine; DMSO: dimethyl sulfoxide; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; ERBB2: erb-b2 receptor tyrosine kinase 2; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MTOR: mechanistic target of rapamycin kinase; PARP1: poly(ADP-ribose) polymerase 1; PI: propidium iodide; SQSTM1/p62: sequestosome 1; TNBC: triple-negative breast cancer